Pendampingan Metode An-Nahdliyah dalam Meningkatkan Kualitas Pengajaran Guru Taman Pendidikan Al-Qur'an - Indarinul Mufidah, Luluk; Wijayanti, Lulud (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service aims to find out the intensive training method of An-Nahdliyah in improving the teaching quality of Darul Falah TPQ Teachers in Pandanarum Village, Baron District, Nganjuk Regency. First, to find out the application of the An-Nahdliyah method in learning to read the Al-Qur'an at TPQ Darul Falah in Pandanarum Village, especially TPQ teachers. Second, to determine the level of understanding in learning to read the Al-Qur'an through the An-Nahdliyah method at TPQ Darul Falah in Pandanarum Village. Third, find out the governance of TPQ Darul Falah in Pandanarum Village, Baron District, Nganjuk Regency. The strategy we use is using a Participatory Action Research (PAR) based method, where teacher participants or TPQ administrators act as facilitators in exploring and discovering the potential that exists in society. The beginning of the above activities is that PAR activities begin with data mining through observation and interviews on the dominant problems in Pandanarum Village, especially those that will later be raised as the main problem. From the results of observations and interviews, data processing was then carried out. The PAR team in Pandanarum Village immediately followed up on the problems that were most urgent and capable of being resolved by carrying out actions relevant to these problems with the community. The findings in this service show that first, there is an increase in understanding of Al-Qur'an teachers in Pandanarum Village, Baron District, Nganjuk Regency. Second, the quality of learning and teaching at TPQ and TPQ in Pandanarum Village, Baron District, Nganjuk Regency can enable students to understand Al-Qur'an skills. Third, increasingly professional governance in TPQ and TPQ in Pandanarum Village, Baron District, Nganjuk Regency.